PENGUKURAN DAN BENCHMARKING EFISIENSI PARIWISATA DI PULAU JAWA-BALI-NUSA TENGGARA MENGGUNAKAN DATA ENVELOPMENT ANALYSIS TAHUN 2013-2017 - Wicaksana, Arif Kurnia; Fatoni, Erma Ziamah (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Tourism resources owned by the government and the private sector often ignore the proper aspects.The use of uncontrolled inputs is the beginning of the inefficiency of tourism activities, which impact the non-optimal output produced. This research aims to identify the efficiency level of government financial management in the tourism sector supported by the provision of tourism facilities to tourist visits and regional revenues from the tourism sector in Java, Bali, and the Nusa Tenggara Islands. The research method used is Data Envelopment Analysis Input-Oriented Constant Return to Scale Model with a quantitative descriptive approach. The results showed that the provinces of DKI Jakarta, West Java, Central Java, and Banten were relatively efficient in optimizing tourism financing. DKI Jakarta and Banten tended to have stable efficiency, and they are good to be referenced.Managerially, this research offers several suggested recommendations. The local government and private sectors can benchmark the efficiency of the tourism sector based on the pattern of financial management for tourism and the use of other regional inputs identified as efficient. Improving efficiency can be done by minimizing the use of inputs at a fixed level of output. Minimum input is expected to reduce the total cost. Theoretically, the result of this study is very helpful in efforts to develop methods of measuring efficiency in the tourism sector that has not been widely implemented in Indonesia.